Clinical and developmental profile of children with Autism - Mhatre, Sameer Prakash; Natu, Sanjay; Londhe, Sarika; Khan, Sanaa (Indian Journal of Child Health, 2017)
Background: Autism spectrum disorders (ASD) are neurodevelopmental disorders characterized by deficits in reciprocal social interaction as well as communication and a restrictive repertoire of activities. Indian studies on this subject have been few. Objectives: The aim of this study was to assess clinical characteristics of children with ASD in Indian scenario. Methods: We conducted a cross-sectional observational survey in special schools involving diagnosed autistic children, and their parents using a pretested standardized questionnaire based on diagnostic and statistical manual IV criteria. Results: Males (n=25) outnumbered the females (n=11). Only 6 cases (16.7%) were diagnosed as autistic before 3 years of age. 39% cases were detected between ages of 3 and 4.11 years. 22% cases were diagnosed in each of 5-6.11 years and 7 years and above category. The must watch behavior characteristics that our study found were impaired eye to eye gaze, impaired peer relationships, poor facial expressions, language delay, lack of pretend play, and inflexible adherence to rituals. Conclusion: Clinicians should be educated and encouraged to make timely diagnosis of ASD so as to initiate early interventions for these children.